mHealth Innovation in Asia Grassroots Challenges and Practical Interventions - Baulch, Emma.; Watkins, Jerry; Tariq, Amina; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2018)
This book offers a detailed account of a range of mHealth initiatives across South, Southeast and East Asia. It provides readers with deep insights into the challenges such initiatives face on the ground, and a view of the diverse cultural contexts shaping strategies for overcoming these challenges. The book brings together various discussions on the broader mHealth literature, and demonstrates how a research focus on diverse Asian contexts influences the success and/or failure of current mHealth initiatives. It also highlights the important roles social scientists can play in advancing theoretical approaches, as well as planning, implementing and evaluating mHealth initiatives. The book is a valuable resource for project planners, policy developers in NGOs and government institutions, as well as academics, researchers and students in the fields of public health, communications and development studies. This book is open access under a CC BY license.
Introduction to the Volume -- Section 1: Challenges -- Chapter 1: Barriers to informal mHealth adoption by community health workers in regional Indonesia -- Chapter 2: Take care of your health, this is what the Qur$1 (Ban said - The use of mobile phone among poor rural women with Type-2 Diabetes in Central Java, Indonesia -- Chapter 3: One size does not fit all - The importance of contextually sensitive mHealth strategies for frontline female health workers -- Chapter 4: Chinese Consumers$1 (BPerceptions and Interpretations of Fitness Mobile Apps: Qualitative Insights -- Section 2: Strategies -- Chapter 5: The Path to Scale: Navigating design, policy and infrastructure -- Chapter 6: mHealth, health and mobility - A culture-centered interrogation -- Afterword.s
Keywords: Mass media; Public health; Communication; Communication in economic development; Quality of life; Media Sociology; Public Health; Media and Communication; Development Communication; Quality of Life Research